2015
DOI: 10.1126/scitranslmed.aaa3863
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus NS1 protein activates cells via Toll-like receptor 4 and disrupts endothelial cell monolayer integrity

Abstract: Complications arising from dengue virus infection include potentially fatal vascular leak, with severe disease being linked with excessive immune cell activation. Understanding the underlying triggers of this activation is critical for developing appropriate disease control strategies. We show here that the secreted form of the dengue virus non-structural protein NS1 is a pathogen-associated molecular pattern (PAMP). Highly purified NS1, devoid of bacterial endotoxin activity, directly activated mouse macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
454
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(471 citation statements)
references
References 61 publications
13
454
1
3
Order By: Relevance
“…IL-10 may contribute to disease severity through NS1-induced IL-10 production by monocytes, which in turn suppresses dengue-specific T cell responses (Adikari et al, 2016;Malavige et al, 2013b). Notably, data from animal studies suggest that NS1 activates immunological cascades in monocytes and macrophages leading to the pathologies observed in SD (Chen et al, 2015;Modhiran et al, 2015). In addition to its immunosuppressive roles, IL-10 has recently been reported as a protective mediator against plasma leakage and vascular dysfunction (Cheng & Sharma, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 may contribute to disease severity through NS1-induced IL-10 production by monocytes, which in turn suppresses dengue-specific T cell responses (Adikari et al, 2016;Malavige et al, 2013b). Notably, data from animal studies suggest that NS1 activates immunological cascades in monocytes and macrophages leading to the pathologies observed in SD (Chen et al, 2015;Modhiran et al, 2015). In addition to its immunosuppressive roles, IL-10 has recently been reported as a protective mediator against plasma leakage and vascular dysfunction (Cheng & Sharma, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two independent studies reported the potential for the virus-encoded NS1 protein to directly contribute to dengue disease pathogenesis (35,36). The study by Modhiran and colleagues (35,36) demonstrated that NS1 is a pathogen-associated molecular pattern that recognizes TLR4 in target cells, which can lead to release of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a dose-dependent release of proinflammatory cytokines, such as IL-6 and TNF-α, was observed in the S.Int. of the AG129 mouse model (35,36) in these studies. These observations support the present study, irrespective of whether AG129 mice were infected with a mouseadapted strain (17) or clinical isolate of DENV2 (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este fenómeno se ha denominado "pecado original antigénico" y puede jugar un papel importante en la inmunopatogénesis del dengue grave, ya que dicha respuesta puede suprimir o retrasar la eliminación del virus, llevando a un incremento en la carga viral y en la inmunopatogénesis de la infección 22 . Igualmente, reportes recientes han demostrado que la proteína viral NS1 posee alta capacidad inmunogénica, contribuyendo mediante distintos mecanismos, con la aparición del fenómeno de permeabilidad vascular por afectación de las células endoteliales, relacionándola directamente con la inmunopatogénesis del dengue grave 21,23,24 . Pero cualquiera que sea el mecanismo por el cual sobreviene la hemorragia, en última instancia, el blanco es el endotelio, convirtiéndolo en un tejido que juega un papel muy importante en la patogénesis del dengue grave.…”
Section: Proteína No Estructuralunclassified